Economic analysis of costs and returns of milk production in Andhra Pradesh - Konda, Ramanjaneya Reddy; Kundu, Ajmer Singh; Biswajit sen; Udita Chaudhary (Indian Journal of Dairy Science, 2024)
The present study was conducted in the Chittoor and East Godavari districts in the state of Andhra Pradesh to estimate the costs and returns of milk production to know the status of milk profitability among the farmer-producer households. The milk productivity in the study area was higher in crossbreed cows than the buffalo and indigenous cattle. The overall gross cost of milk production was ₹ 264.40 per animal per day, which was higher in the crossbreed cows than the other species of animals. The variable costs account for the major proportion of the cost of milk production with about 88.87 percent than the fixed cost of 11.13 percent. In the variable costs, feed and fodder costs occupy the major share of 71.89 percent of the cost of milk production than the labour costs and the veterinary and miscellaneous costs. The average milk production per animal was 7.23 litres per day, was highest in the crossbreed cows with 10.37 litres per day than in buffalo (6.12 litres per day) and indigenous cattle (5.21 litres per day). The overall net returns per animal were highest in crossbreed cows with ₹ 83.14 per day than the buffalo (₹ 51.66 per day) and the indigenous cattle (15.66 per day). The cost of milk production and net returns per litre was highest in the buffalo with ₹ 44.89 per litre and ₹ 8.37 per litre than the crossbreed cows and the indigenous cattle. Even though the overall returns from milk production were positive among all the farmer-producer households in the study area rearing of crossbreed cows and buffalo was found to be profitable more than the indigenous cattle.